2013
DOI: 10.1111/ele.12233
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory makes major contributions to ecosystem carbon and nutrient cycling in tropical forests

Abstract: The functional role of herbivores in tropical rainforests remains poorly understood. We quantified the magnitude of, and underlying controls on, carbon, nitrogen and phosphorus cycled by invertebrate herbivory along a 2800 m elevational gradient in the tropical Andes spanning 12°C mean annual temperature. We find, firstly, that leaf area loss is greater at warmer sites with lower foliar phosphorus, and secondly, that the estimated herbivore-mediated flux of foliar nitrogen and phosphorus from plants to soil vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
188
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 205 publications
(194 citation statements)
references
References 53 publications
3
188
1
2
Order By: Relevance
“…As an illustration of the potential significance of this finding for ecosystem carbon cycling, we conducted a simple scaling exercise. Assuming typical foliar biomass-C (* 400 kg ha -1 , Kjelvik and Kären-lampi 1975), outbreak defoliation rates (* 75%, Olsson et al 2017), and insect respiration (* 20%, Metcalfe et al 2014), this means that an additional * 100 kg C ha -1 would be released during outbreaks via insect or microbial respiration that would otherwise have remained relatively inert as leaf litter. This would correspond to roughly to a 30% decrease in soil C-accumulation from aboveground litter.…”
Section: Discussionmentioning
confidence: 99%
“…As an illustration of the potential significance of this finding for ecosystem carbon cycling, we conducted a simple scaling exercise. Assuming typical foliar biomass-C (* 400 kg ha -1 , Kjelvik and Kären-lampi 1975), outbreak defoliation rates (* 75%, Olsson et al 2017), and insect respiration (* 20%, Metcalfe et al 2014), this means that an additional * 100 kg C ha -1 would be released during outbreaks via insect or microbial respiration that would otherwise have remained relatively inert as leaf litter. This would correspond to roughly to a 30% decrease in soil C-accumulation from aboveground litter.…”
Section: Discussionmentioning
confidence: 99%
“…Partial leaf damage (holes in fallen leaves) was estimated at ca. 0.8 Mg C ha −1 yr −1 in a lowland Peruvian forest (Metcalfe et al, 2013); in addition, leaf-monitoring studies (Lowman, 1984;Filip et al, 1995) have shown that an equivalent amount or more may typically be lost to herbivores that remove entire leaves.…”
Section: Leaf Litterfall (Vs Leaf Production)mentioning
confidence: 99%
“…All herbivores consume and digest autotroph biomass, and release nutrients, e.g., nitrogen (N) and phosphorus (P), in wastes through excretion (urine) or egestion (feces). Nutrient release by herbivores can strongly impact nutrient availability for autotrophs in terrestrial, marine, and freshwater ecosystems (Pastor et al, 1993;McNaughton et al, 1997;Covich et al, 1999;Sirotnak and Huntly, 2000;Hunter, 2001;Vanni, 2002;Bardgett and Wardle, 2003;McIntyre et al, 2007;Cech et al, 2008;Roman and McCarthy, 2010;Metcalfe et al, 2014;Turner, 2015;Doughty et al, 2016). The ratio of N to P released (i.e., waste N:P) may be crucial for mediating ecosystem impacts of herbivore-driven nutrient recycling (Sterner, 1990;Urabe et al, 1995;Elser and Urabe, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, herbivore-driven nutrient recycling also likely plays a major role in terrestrial ecosystems (Pastor et al, 1993;McNaughton et al, 1997;Hunter, 2001;Wardle et al, 2004;Metcalfe et al, 2014;Doughty et al, 2016). Indeed, the ratio of carbon (C) to nutrient (N and/or P) in plant tissues has long been recognized as an important determinant of herbivore feeding selectivity and subsequent nutrient cycling and availability in terrestrial ecosystems (Ritchie et al, 1998;Pastor et al, 2006;Bakker et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%